2020
DOI: 10.1289/ehp5117
|View full text |Cite
|
Sign up to set email alerts
|

Independent and Combined Effects of Heatwaves and PM2.5 on Preterm Birth in Guangzhou, China: A Survival Analysis

Abstract: BACKGROUND: Both extreme heat and air pollution exposure during pregnancy have been associated with preterm birth; however, their combined effects are unclear. OBJECTIVES: Our goal was to estimate the independent and joint effects of heatwaves and fine particulate matter [PM <2:5 lm in aerodynamic diameter (PM 2:5 )], exposure during the final gestational week on preterm birth. METHODS: Using birth registry data from Guangzhou, China, we included 215,059 singleton live births in the warm season (1 May-31 Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 51 publications
5
69
1
Order By: Relevance
“…Specifically, heatwave associations were larger in magnitude among Hispanic and non-Hispanic black mothers compared to non-Hispanic white mothers. In several previous studies, investigators reported positive associations between heatwaves and preterm birth, with larger magnitudes compared to our study [ 9 , 11 , 13 , 19 – 22 , 42 ]. In the current study, we observed only a slight overall increase in the risk of preterm birth for certain heatwave definitions, and most estimates were close to the null.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Specifically, heatwave associations were larger in magnitude among Hispanic and non-Hispanic black mothers compared to non-Hispanic white mothers. In several previous studies, investigators reported positive associations between heatwaves and preterm birth, with larger magnitudes compared to our study [ 9 , 11 , 13 , 19 – 22 , 42 ]. In the current study, we observed only a slight overall increase in the risk of preterm birth for certain heatwave definitions, and most estimates were close to the null.…”
Section: Discussioncontrasting
confidence: 71%
“…However, no consistent epidemiological evidence suggests that extreme temperature should have a greater impact on births later in gestational age (e.g., late preterm (34–36 weeks) and early-term birth (37–38 weeks)) compared to those in early gestation (e.g., extremely preterm (< 28 weeks) and very preterm (28–32 weeks)). Some studies observed stronger associations of temperature among early preterm birth [ 11 , 14 , 19 ], while others found the opposite [ 22 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…those of PM2.5, have been shown to have been in the 1980's twice as high, compared with the corresponding pollutant levels in the same region during the second decade of the 21st century (Kukkonen et al, 2018). Wang et al (2020) presented that PM2.5 exposure strengthened the effect of moderate heat waves (short or only moderate temperature rise) associated with preterm births during January 2015 -July 2017 in Guangdong province, China. However, during the intensive heat waves, the effects were not additive.…”
Section: (I) the Role Of Air Pollution In Pandemicsmentioning
confidence: 99%
“… 3 , 4 A retrospective cohort study published in Environmental Health Perspectives looked at the relationship between fine particulate matter ( ) combined with heatwaves and the risk of preterm birth in Guangzhou, China. 5 …”
mentioning
confidence: 99%